Slugging It out: Fine Tuning the p53-PUMA Death Connection - Zilfou, Jack T. (Cell, 2005)
In response to DNA damage, the tumor suppressor p53 elicits a complex cellular response. In this issue of Cell, Wu et al. (2005) show that the transcription factor SLUG is induced by p53 and protects hematopoietic progenitor cells from apoptosis triggered by DNA damage. SLUG exerts this protective role by repressing Puma, a proapoptotic target of p53. PUMA is also a key coordinator of apoptosis mediated by both nuclear and cytoplasmic functions of p53 (Chipuk et al., 2005).